Upaya Pemecahan Masalah Dalam Pembelajaran Matematika Untuk Meningkatkan Hasil Belajar Siswa MTsN 3 Kota Jambi - Cunus Sa'adah; Amir Mahmud (Universitas Muhammadiyah Makassar, 2021)
In this research, we are trying to find out whether problem solving is utilized in mathematics training to improve students' performance at MTsN 3 Jambi City Problem solving is done by focusing students' attention on a particular concern, encouraging them to analyze the problem, and getting them to learn about and discover solutions. Processing is the information means mixing mental processes and physical actions to arrive at a solution. the students' performance in mathematics proved' Significant correlation is shown by the findings of the seventh grade students